(untitled) (Религиски дијалог и соработка, 2023)
Religious tolerance continues to grow today, but at a moderate pace. Even after the International Conference of Religious Tolerance in the Light of Human Rights in 1995 in the capital of Bulgaria – Sofia the question of studying religious tolerance between different religious communities arose. New times open a wider horizon of worldview and new generations become more responsive and tolerant of new personalities and religion movements. In the increasingly global world in which we live, we are confronted every day with different attitudes in the relations between different religious communities, their traditions and customs. Unfortunately, there is both religious tolerance and religious intolerance. This study aims to show religious tolerance now and how different religious groups live together side by side. Many new religious movements have emerged in the last few years. These religious movements are more or less accepted by different generations society. The sooner we seek answers to important questions such as peace and harmony between different religious communities and its implementation the sooner other answers will emerge. We are all different as individuals, different in religion and understanding of life. This is a root of the secret of our earthly path in the application of sharing, tolerance, respect of each other. However, there is still an imposition in human relationship. Quantitative method was used. Secondary data analysis is performed. Religious tolerance will always be a leading topic for reflections between the struggle between good and evil, the difference between white and black or the meaning of the eastern symbol “yin and yang”. Above all leading should be what kind of person you define yourself and what is your attitude to the color world around you.